Land disputes on the outskirts of Istanbul: a unique case of legalization amidst demolitions and forced evictions - Cabannes, Yves; Goral, Ozgur Sevgi (SAGE PUBLICATIONS LTD, 2020)
This paper focuses on struggles for land by ordinary people in globalizing cities. By drawing on three cases in Istanbul, it explores the circumstances under which these struggles can be successful. It analyses the evolution of the self-built settlements of Ayazma, Yakacik and Hurriyet and their varied outcomes, from legalization to razing. Three conditions seem to explain why land titling was obtained in Yakacik and proved impossible elsewhere. One is specific to land ownership. The second reason revolves around the mediating role and political commitment of a district municipality, primarily through the engagement of one of its decision-makers in favour of poor residents. The third reason relates to the nature and form of Yakacik residents' mobilization and organizations. All of these conditions are essential; none is sufficient individually. The difficulty of bringing all these conditions together at one time and in one place explains the exceptional nature of the case in point.
Keywords: forced evictions; gecekondu; Istanbul; land legalization; planning; self-built popular neighbourhoods; state mediation; urban struggles; Environmental Sciences & Ecology; Urban Studies